Prevalence and risk factors associated with self-reported psychological distress among college students during the omicron outbreak in Shanghai - Li, Wei (Frontiers in Public Health, 2022)
Background More and more attention has been paid to the mental health of students in higher education. The Omicron outbreak has brought renewed attention to this vulnerable group. Objective To understand the prevalence and influencing factors of anxiety symptoms and depression symptoms of college students in a closed state. Methods This large cross-sectional study using data from a survey on the mental health of college students in Shanghai (China), conducted by using a stratified cluster random sampling method between March 15th and April 15th, 2022. To estimate results related to regional location, only data from students with Internet protocol addresses and current addresses in Shanghai were included. The main outcome was self-reported psychological distress (including depressive symptoms, anxiety symptoms, and self-assessment of health), measured using the epidemiologic studies depression scale (CES-D), the Spielberger state-trait anxiety inventory (STAI) and self-rated mental health (SRMH), respectively. Moreover, the Simplified Coping Style Scale (SCSS) was also used to assess how participants coped with negative emotions. Results Among 13,000 college students who completed the survey, 12,124 students were included in the final analysis, and the total effective rate was 93.3%. The prevalence of depressive symptoms and anxiety symptoms were 14.1 and 9.8%, respectively. By using Multivariate logistics regression analysis, we found that being male and negative coping were risk factors for depressive symptoms and anxiety symptoms, while positive coping, such as study or learning, were protective factors. Moreover, linear regression analysis showed that learning or study improved the overall mental health index by improving anxiety or depressive symptoms, and played a partial mediating role. Conclusions These findings suggest that a significant number of college students, especially boys, will experience emotional problems during the course of closed schools. Therefore, we need to give them proper attention and advise them to adopt positive coping strategies, such as learning or study, to resist bad emotions.